The New Global Challengers and the Competition Paradigm: Where Does the World Stand Today? - Lévy, Brigitte (Université d'Ottawa | University of Ottawa, 2010)
Emerging countries are changing world competition dynamics on a scale never witnessed before. Also, the international economic system and the supporting institutions are under pressure. We are in the midst of profound changes in the way business is conducted across borders, and finding a path for sustainable development remains a critical issue. The paper first looks at the positioning of multinational corporations (MNCs) from emerging countries in the world arena. Then, it considers the new paradigm of global competition and the way it affects trade relations. Last, it reflects upon the challenges ahead in the multipolar economy of the 21st Century.